Contextual Variables Affect Running Performance in Professional Soccer Players: A Brief Report - Diêgo Augusto; Diêgo Augusto; Diêgo Augusto; João Brito; Rodrigo Aquino; Pedro Figueiredo; Pedro Figueiredo; Pedro Figueiredo; Fabio Eiras; Márcio Tannure; Bruno Veiga; Bruno Veiga; et al. (Frontiers Media S.A., 2021)
This study aimed to investigate the effects of contextual variables on running performance in Brazilian professional soccer players. Twenty male players from one club participating in the 1st Division of the Brazilian soccer championship were analyzed during 35 matches. Global Positioning System was used to determine total distance (TD) covered, distance covered and actions in high intensity and sprinting, and the number of accelerations, and decelerations. The independent variables used were match location, match outcome, opposition ranking, change of head coach, and distance traveled to play the matches. Total distance was higher in a way than home matches (9,712 vs. 9,533 m; p ≤ 0.05), and losses than draws and wins (9,846 vs. 9,400 vs. 9,551 m; p ≤ 0.05), whereas distance in sprinting was higher in draws than losses (203 vs. 175 m; p ≤ 0.01). Changing the head coach during the season resulted in overall lower distance covered in high intensity, sprinting, high-intensity actions (p ≤ 0.01), and decelerations (p ≤ 0.05). Higher values for distance covered in sprinting and high intensity were found in matches without travel compared to those with long-travel (p ≤ 0.05). Overall, running performance was affected by the location, match outcome, change of head coach, and distance traveled during the season.